IMPLEMENTASI METODOLOGI SCRUM DALAM PENGEMBANGAN APLIKASI EREGITRASI VENDOR (STUDI KASUS : KRAKATAU IT) - Roy Amrullah Ritonga; Asep Mabrur A'id; Anita Megayanti (Program Studi Sistem Informasi, Universitas Banten Jaya, 2021)
Vendor registration is an online-based vendor registration application designed under the web using a frame work codeigniter and is part of the eprocurement application. Eregistration was developed as an effort to use master vendors in all activities in following the procurement process for goods and service providers to become partners of PT. Krakatau IT. In the Application Development Process, vendor registration uses the Scrum method which aims to complete the speed of development. The implementation of the Scrum method is indispensable in the process of developing the registration which has a medium-scale work scope and is done in team work so that it can be completed for 3 (three) months. This vendor registration development uses a sprint based on workload priorities that will be included in the product backlog. Some of the scrum methods that the researcher will discuss include the Product Backlog, Sprint Backlog and deliverables.